Large epigenome-wide association study identifies multiple novel differentially methylated CpG sites associated with suicidal thoughts and behaviors in veterans - Kimbrel, Nathan A.; Garrett, Melanie E.; Evans, Mariah K.; Mellows, Clara; Dennis, Michelle F.; Hair, Lauren P.; Hauser, Michael A.; , the VA Mid-Atlantic MIRECC Workgroup; Ashley-Koch, Allison E.; Beckham, Jean C.; Beckham, Jean C.; Calhoun, Patrick S.; et al. (Frontiers in Psychiatry, 2023)
Introduction: The U.S. suicide mortality rate has steadily increased during the past two decades, particularly among military veterans; however, the epigenetic basis of suicidal thoughts and behaviors (STB) remains largely unknown. Methods: To address this issue, we conducted an epigenome-wide association study of DNA methylation (DNAm) of peripheral blood samples obtained from 2,712 U.S. military veterans. Results: Three DNAm probes were significantly associated with suicide attempts, surpassing the multiple testing threshold (FDR q-value < 0.05), including cg13301722 on chromosome 7, which lies between the genes SLC4A2 and CDK5; cg04724646 in PDE3A; and cg04999352 in RARRES3. cg13301722 was also found to be differentially methylated in the cerebral cortex of suicide decedents in a publicly-available dataset (p=0.03). Trait enrichment analysis revealed that the CpG sites most strongly associated with STB in the present sample were also associated with smoking, alcohol consumption, maternal smoking, and maternal alcohol consumption, whereas pathway enrichment analysis revealed significant associations with circadian rhythm, adherens junction, insulin secretion, and RAP-1 signaling, each of which was recently associated with suicide attempts in a large, independent genome-wide association study of suicide attempts of veterans. Discussion: Taken together, the present findings suggest that SLC4A2, CDK5, PDE3A and RARRES3 may play a role in STB. CDK5, a member of the cyclin-dependent kinase family that is highly expressed in the brain and essential for learning and memory, appears to be a particularly promising candidate worthy of future study; however, additional work is still needed to replicate these finding in independent samples.